TiSi2-SiC agglomerates toughened TiC composites prepared by in-situ reaction under high pressure. Issue 4 (2nd October 2019) - Chen, Qingyun; Liu, Lixin; Xu, Beibei; Meng, Chuanmin; Li, Xuhai
ABSTRACT: Almost completely dense (>99%) TiC composites toughened by TiSi2 -SiC agglomerates were fabricated by high pressure in-situ reaction sintering of TiC and Si at a lower temperature of 1150°C. In the agglomerates of TiSi2 and SiC interlocking structures, the size of TiSi2 particles is controlled on the nanometer and submicron scales. The precursors used in the preparation were TiC and Si. The addition of Si in the precursor can effectively improve the sintering activity of TiC ceramic. Doping a certain amount of Al and increasing the sintering pressure can significantly improve the toughness of the composite. For the first time, TiSi2 -SiC composites were introduced into TiC ceramics, which greatly inproved the toughness of TiC ceramics.